Role of Nerve Conduction Velocity and Pre Albumin to Fibrinogen Ratio in Diagnosing Diabetic Polyneuropathy: A Comparative Analytical Study - Suchitra Palve, Sachin Palve (International Journal of Modern Agriculture, 2020)
Background: In the current millennial era, diabetes mellitus has emerged as a global pandemic accounting for multiple morbid complications. Diabetic polyneuropathy (DPN) is one such disabling complication. Aim and objectives: To analyse and compare the association between pre albumin to fibrinogen ratio (PFR) and electro diagnostic test among diabetes mellitus patients. Material and methods This present study was taken up in a Mahatma Gandhi Medical College Hospital and Research Institute. Over hundred (100) diabetes mellitus patients were enrolled along with an equal number of control group individuals. Different parameter which including, electrophysiological analysis in the form of nerve conduction studies, perception threshold for vibration (VPT), biochemical as well as hematological parameters, including fibrinogen levels were assessed. Depending on the values of pre albumin to fibrinogen ratio, patients were categorized in various groups. Clinical parameters were assessed in both groups. Results: Age (P<0.002), duration of disease (P<0.002), Creatinine levels (P=0.008) and NLR levels (P<0.001) among diabetic group was significantly higher. DPN group was significantly higher, while FPG (P=0.041), TC (P=0.027), AFR (P<0.001) and PFR (P<0.001) was reduced significantly. The percentage of DPN and VPT in the lowest PFR tertile was significantly higher than that in the middle PFR tertile and the highest PFR tertile (P<0.001). NCV in the lowest PFR tertile was significantly lower than that in the middle PFR tertile and the highest PFR tertile between (P<0.01-0.003).Correlation analysis showed that PFR were negatively associated with the VPT (P<0.001), while nerve conduction velocity for median motor and sensory nerve, for peroneal motor and sensory nerve (P<0.001) was positively correlated with PFR , Once these values were adjusted to potentially related factors, PFR is independently correlated to diabetic polyneuropathy (P=0.008). The area under the ROC curve was 0.627. Conclusion: This study will be first of its kind which proves that PFR can be a key component associated with DPN in T2DM,